Study the Effect of some Medical Plants in Biofilm Formation and Antibiotic Sensitivity for Klebsiella Pneumoniae - Ibrahim , Israa AJ. (Iraqi Journal of Science, 2021)
Twenty clinical and fecal samples (ten clinical samples from patients attending toImam Ali Hospital and ten chicken faeces samples collected from local poultry farmin Baghdad city) collected during December 2015, for isolated Klebsiellapneumoniae. All K. pneumoniae isolates were extended-spectrum β- lactamaseproducers and biofilm formation. The activities of two selected K. pneumoniaeisolates for their biofilm formation and susceptibility to antibiotics after treatmentwith several plants extracts were investigated. The results of water and 60% ethanolextracts for Matricaria chamomile flowers, Alhagi maurorum leafs, Syzygiumaromaticum buds (clove) and Arctium minus leafs were showed reduction of biofilmformation and change the ability of antibiotic susceptibility for these two tested K.pneumoniae isolates. The indirect effect of plants extracts on the bacterial growthmay be causing indirect effect on the metabolic activity and DNA (chromosome orplasmid) of cells. All tested plant extract contain many antimicrobial and antioxidantcomponent by using GC-mass.